History captured in a net. Displacement in hypertext Wikipedia - Smyčka, Václav (Dějiny – teorie – kritika, 2014)
In his study, Václav Smyčka shows how the issue of the expulsion of Germans from Czechoslovakia after the Second World War is dealt with in the Wikipedia hypertext. The author traces the negotiation of the specific form of selected articles on the topic, pointing out a certain interpretive conservatism of Wikipedia, determined by the concern of its core users for the non-controversiality of texts. At the same time, it compares entries formulated in general terms with those narrowly thematic, all in their Czech and German language versions. Smyčka concludes that the distinctly asymmetrical arrangement of these articles in the two language forms itself determines the interpretation of the history within the hypertext and thus the resulting reader's opinion.